«Білоруське Купалля» на північному заході сучасної Волині - Келемен, Юлія Іванівна; Kelemen, Yuliya (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розглядається механізм упровадження білоруських традицій та новацій у купальський обряд сіл Ратнівського, Старовижівського, Шацького районів Волинського Полісся. Головним детермінатором, на думку автора, стала художня самодіяльність 60–70-х років минулого століття. Заради досягнення більшої видовищності в сценарій свята залучався матеріал, запозичений у сусідів. У такий спосіб набули поширення такі елементи, як звезення мотлоху на купальський вогонь за допомогою воза, у який впрягалися хлопці, вбивання в землю жердини, довкола якої складалося паливо, та зв’язування в її верхній частині «крижа», обвитого вінками, що нагадував сонце, яке грає, розпалювання одного загального вогнища замість кількох, залучення до виконання купальських пісень хору.The customs of Kupala in the villages of Ratne, Stara Vyzhva and Shatsk districts of Volyn Polissya differ significantly from those that are practiced on the rest of the territory of the region. The author believes that the reason why the new elements of the custom appeared and some old traditional ones were forgotten is that they were loaned from Belarussian amateur arts, which only strive for entertainment. This process has started in the 60th–70th of the last century. The respondents, who were the main participants of these celebrations reproduce this particular scenario. This way several elements, such as delivering useless belongings by cart pulled by the boys to Kupala bonfire, hammering a pole into the ground, putting whatever was to be burnt around it, attaching “kryzh” which was tied up with the wreaths, resembling the play of the sun, on top of the pole, setting one general bonfire instead ofseveral ones, and having a choir singing kupala songs, were circulated. In these districts kupala custom is practiced in just several villages, mostly located close to the border, particularly in Hutj of Ratne district kupala songs are called petrivky, which proves that the custom is not traditional, in Pishcha of Shatsk district, where these activities are observed from at least the beginning of the XX century, in the villages called Yarevyshche of Stara Vyzhva district, where within the last years certain objectswere Christianized, for instance installation of the icons into “kupailytsya” – the willow branch decorated with the flowers, which is considered to be the main element of this holiday in Volyn and is almost not known in Western Polissya. However in Myziv of Stara Vyzhva district, which is located further from Ukrainian-Belarussian administrative border, the old traditions are forgotten and the new ones haven’t been applied. This is an additional proof that they were introduced artificially.
“Belarussian Kupallia” on the North-Western Part of Modern Volyn
Keywords: Купала; Волинське Полісся; білоруські традиції та новації; художня самодіяльність; Kupala; Volyn Polissya; Belarusian traditions and innovations; amateur performances